Dynamic Revealed Comparative Advantage: Export Potential Crude Palm Oil (CPO) Indonesia Database 2018 - Betrix Silitonga; Natalia Artha Malau; Garan Paruta; Ivan Hannoeriadi Ardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
As the largest CPO exporter country in the world, Indonesia's CPO production is increasing every year. Even though Indonesia's CPO production has increased, Indonesia's CPO has a slow growth rate, low productivity and the competitiveness of Indonesian CPO to destination countries has not increased. The purpose of this research is to analyze the factors that influence the competitiveness of Indonesian CPO and formulate policies that can increase the competitiveness of Indonesian CPO. Quantitative analysis uses Stata 14 along with panel data with the 2018 database. Export volume growth, selling prices, inflation and population growth in importing countries have a negative effect on the competitiveness of CPO export commodities while GDP growth in importing countries and exchange rates have a positive relationship to competitiveness CPO export commodity.